STRATEGI PENGHIMPUNAN DAN PENYALURAN DANA INFAQ MELALUI LAZNAS DALAM PERSPEKTIF EKONOMI ISLAM - Nugroho, Abdurrahman Putera; Mada, Gama; Shapira, Nadia (Taksasila Edukasi Insani, 2024)
This research discusses strategies for collecting and distributing infaq funds through the national zakat amil institution (LAZNAS) from an Islamic economic perspective. Infaq has an important role in creating social welfare, but its management often faces challenges in terms of efficiency and transparency. Effective strategies include community empowerment, use of digital technology, and collaboration with the private sector. The distribution of infaq funds needs to be carried out transparently and on target to support economic empowerment, education and health programs. Even though there are challenges such as a lack of public trust, with good management, infaq funds can be used optimally to achieve fair socio-economic goals in an Islamic economy. Keywords: Collection Strategy, Fund Distribution, Infaq, Islamic Economics, LAZNAS